2008
DOI: 10.1149/1.2943245
|View full text |Cite
|
Sign up to set email alerts
|

Superior Capacitive Performance of Aligned Carbon Nanotubes in Ionic Liquids

Abstract: Electrodes and electrolytes are two essential components of a supercapacitor and play important roles in determining the performance for the supercapacitor. In the present work, we investigated the electrochemical and capacitive behavior of aligned carbon nanotube electrodes in ionic liquid electrolytes to study the feasibility to develop high performance supercapacitors from these two components. Synthesis procedure of the carbon nanotubes and composition of the ionic liquids have been studied to achieve a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…As expected, recent research has indicated that ther improved rate capability of VA-CNTs over random CNTs can be achieved for a three-electrode system using a liquid electrolyte. 68,72,[74][75][76] Specically, a high capacitance of 365 F g À1 has been obtained in 1 M H 2 SO 4 for a VA-CNT array electrode prepared by template-assisted CVD 75 and 440 F g À1 for a VA-CNT electrode in ionic liquid electrolytes 62 prepared by a template-free CVD approach. 72,76 However, VA-CNTs, either with their tip opened or closed, have hardly been exploited for applications in twoelectrode all-solid-state supercapacitors, which would surely further enhance the performance of the exible device.…”
Section: Cnt-based Exible Supercapacitorsmentioning
confidence: 95%
“…As expected, recent research has indicated that ther improved rate capability of VA-CNTs over random CNTs can be achieved for a three-electrode system using a liquid electrolyte. 68,72,[74][75][76] Specically, a high capacitance of 365 F g À1 has been obtained in 1 M H 2 SO 4 for a VA-CNT array electrode prepared by template-assisted CVD 75 and 440 F g À1 for a VA-CNT electrode in ionic liquid electrolytes 62 prepared by a template-free CVD approach. 72,76 However, VA-CNTs, either with their tip opened or closed, have hardly been exploited for applications in twoelectrode all-solid-state supercapacitors, which would surely further enhance the performance of the exible device.…”
Section: Cnt-based Exible Supercapacitorsmentioning
confidence: 95%
“…CNTs can be produced using various methods, including carbon arc discharge, 349,350 pulsed laser vaporization, 351,352 pyrolysis of hydrocarbons 353 to produce SWNTs, CVD for aligned MWCNT, 354,355 and plasma-enhanced CVD approach for aligned SWNTs. 356 CNTs are desirable electrode materials due to their unique characteristics, including high specific surface area, mesoporosity, strong electrical conductivity, and charge transfer capacity.…”
Section: Activated Carbons (Acs)mentioning
confidence: 99%
“…CNTs can be produced using various methods, including carbon arc discharge, 349,350 pulsed laser vaporization, 351,352 pyrolysis of hydrocarbons 353 to produce SWNTs, CVD for aligned MWCNT, 354,355 and plasma-enhanced CVD approach for aligned SWNTs. 356…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%